(untitled) (MASKAY, 2025)
This paper presents a systematic review of relevant studies published between 2019 and 2024, focusing on data security protocols in cloud computing environments. The selection process was based on rigorous criteria to identify the most relevant features of these protocols and their current applications. The review examines their advantages as well as the cryptographic mechanisms used to protect sensitive data, including Advanced Encryption Standard (AES), Rivest–Shamir–Adleman (RSA), and Elliptic Curve Cryptography (ECC). Additionally, the increasing use of Kubernetes as a container orchestration tool is analyzed, acknowledging its significance in modern cloud infrastructures. Within this context, several studies are reviewed that highlight implementation limitations such as inadequate privilege management and the reliance on third-party solutions. This research aims to provide a comprehensive understanding of current trends and challenges in cloud data security and to support the identification of potential strategies to address these issues and enhance the robustness of cloud-based security architectures.